The Immunology of Autoimmune Thyroid Disease in Pregnancy - Balucan, Francis; Davies, Terry F. (Journal of the ASEAN Federation of Endocrine Societies, 2014)
In pregnancy, complex physiologic changes in the immune system alters the environment for the “non-self” fetus allowing it to be tolerated in the maternal womb, while the immune system is still able to counteract external pathogens. The interplay of the immune system and the physiologic changes induced by pregnancy on the thyroid induce changes in the natural history of the autoimmune thyroid diseases (AITD). This review discusses the various players in creating this milieu, including the MHC, the T- and B-cells, sex steroids and the possible role of microchimerism. The participants provide a variety of mechanisms that create the clinical scenarios that we see in patients with AITD – most commonly the improvement in Grave’s Disease during pregnancy and the rebound in thyroid autoantibodies and recurrence, or new onset, of Graves’ and Hashimoto’s diseases in the post-partum.